Optical glass, glass preform, optical element and optical instrument
By rationally designing the component ratio of optical glass, the mid-infrared transmittance and hardness are improved, and the problem of poor imaging quality of existing optical glass in the mid-infrared band is solved, and it is suitable for high-performance mid-infrared optical systems.
Patent Information
- Application Number
- CN202510092985.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing mid-infrared transmission optical glass has problems such as low transmittance, low refractive index and poor mechanical properties, which affects the clear and stable imaging of optical equipment in the mid-infrared band.
By rationally designing the components of optical glass, the cationic components contain Ge4+, Ba2+, Zn2+, La3+, Al3+ and Ga3+, the anionic components contain O2- and F-, and the content ratio of each component is controlled to improve the transmittance, refractive index and hardness of the glass.
It realizes the higher mid-infrared transmittance and hardness of optical glass, meets the needs of high-performance mid-infrared optical systems, and is suitable for mid-infrared imaging.
Smart Images

Figure CN119874189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an optical glass, in particular to a mid-infrared transmission optical glass with higher transmittance and higher hardness, and a glass preform, an optical element and an optical instrument made of the optical glass. Background Art
[0002] The 2-5μm mid-infrared band contains the transparent transmission window of the atmosphere, and is less disturbed by scattering when transmitted in the air. It plays an important role in the fields of communication remote sensing, environmental monitoring, infrared reconnaissance and tracking, infrared jamming countermeasures, precision guidance, high-energy laser weapons, etc. Therefore, higher requirements are placed on the performance of optical glass used in the 2-5μm mid-infrared band.
[0003] Transmittance is an important indicator of mid-infrared transparent materials. Mid-infrared transparent optical glass with high transmittance can improve the imaging quality of optical equipment. In addition, the development trend of large field of view and miniaturization of mid-infrared optical systems requires mid-infrared transparent optical glass to have a high refractive index to expand the imaging range and simplify the optical system. At the same time, as the first contact between optical equipment and the external environment, mid-infrared transparent optical glass is required to have good mechanical properties and chemical stability to cope with the direct impact of complex environments on the optical system and ensure clear and stable imaging. The mid-infrared transparent optical glass in the current existing technology has problems such as low transmittance, low refractive index and poor mechanical properties, which affect the clear and stable imaging of optical equipment in the mid-infrared band. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a mid-infrared transmitting optical glass with higher transmittance and higher hardness.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] Optical glass, its composition is expressed in mole percentage, the cationic component contains: Ge 4+ :13~21%;Ba 2+ :4~13%; Zn 2+ : 2~10%; La 3+ : 3~13%;
[0007] The anion component contains: O 2- :43~52%; F - :12~22%.
[0008] Furthermore, the optical glass, whose components are expressed in molar percentage, also contains the following cation components: Al 3+ :0~2%;and / or Ga 3+ :0~3%.
[0009] Optical glass, its components are expressed in molar percentage, the cation component is Ge 4+ :13~21%;Ba 2+ :4~13%; Zn 2+ : 2~10%; La 3+ :3~13%;Al 3+ :0~2%;Ga 3+ : 0~3%, the anion component is O 2- :43~52%; F - : Composition: 12~22%.
[0010] Furthermore, the optical glass has its components expressed in molar percentage, wherein: La 3+ / (Zn 2+ +Ba 2+ ) is 0.2 to 1.4, preferably La 3+ / (Zn 2+ +Ba 2+ ) is 0.3 to 1.2, and more preferably La 3+ / (Zn 2+ +Ba 2+ ) is 0.4~1.0.
[0011] Furthermore, the optical glass, its components are expressed in molar percentage, wherein: Ba 2+ / (Ge 4+ +Ga 3+ +Al 3 + ) is 0.2 to 1.0, preferably Ba 2+ / (Ge 4+ +Ga 3+ +Al 3+ ) is 0.3~0.8.
[0012] Furthermore, the optical glass has its components expressed in molar percentage, wherein: - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.5 to 1.2, preferably F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.6 to 1.1, and more preferably F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.7~1.0.
[0013] Furthermore, the optical glass has its components expressed in molar percentage, wherein:2- / F - 2.0~4.3, preferably O 2- / F - 2.1 to 3.9, more preferably O 2- / F - It is 2.3 to 3.5.
[0014] Furthermore, the optical glass, its components are expressed in molar percentage, wherein: Ge 4+ : 14-20%, preferably Ge 4+ : 15-19%; and / or Ba 2+ : 5-12%, preferably Ba 2+ : 6-11%; and / or Zn 2+ : 3-9%, preferably Zn 2+ : 4-8%; and / or La 3+ : 4-11%, preferably La 3+ : 5-10%; and / or Al 3+ : 0~1%, preferably Al 3+ :0~0.5%;and / or Ga 3+ : 0-2%, preferably Ga 3+ :0~1%;and / or O 2- : 44-51%, preferably O 2- :45~50%;and / or F - : 13-21%, preferably F - :14~20%.
[0015] Furthermore, the refractive index n of the optical glass is d is 1.70 to 1.78, preferably 1.71 to 1.78, more preferably 1.72 to 1.78, and further preferably 1.74 to 1.77; Abbe number ν d It is 42-51, preferably 42-49, more preferably 42-48, and further preferably 43-46.
[0016] Furthermore, the optical glass with a thickness of less than 2 mm has a transmittance of 0.5 to 2.5 μm. 0.5~2.5 83% or more, preferably 85% or more, more preferably 87% or more; and / or a transmittance τ greater than 2.5 μm but less than or equal to 5 μm 2.5~5 is 78% or more, preferably 82% or more, more preferably 85% or more; and / or the wavelength λ corresponding to the mid-infrared transmittance of 50% 50 It is 5.75 μm to 5.8 μm, preferably 5.76 μm to 5.8 μm, and more preferably 5.77 μm to 5.8 μm.
[0017] Furthermore, the thickness of the optical glass is 0.1 to 2 mm, preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.3 mm, 0.5 mm, 1 mm, 1.2 mm, or 1.5 mm.
[0018] Furthermore, the hardness H of the optical glass k 460×10 7 Pa or more, preferably 470×10 7 Pa or more, more preferably 480×10 7 Pa or more, more preferably 480×10 7 Pa~500×10 7 Pa; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A The degree of bubble is above Class 3, preferably Class 2 or above; and / or the degree of bubble is above Class A, preferably above Class A0, more preferably above Class A 00 class.
[0019] The glass preform is made of the above optical glass.
[0020] The optical element is made of the above optical glass, or made of the above glass preform.
[0021] An optical instrument containing the above optical glass or the above optical element.
[0022] The beneficial effects of the present invention are as follows: through reasonable component design, the optical glass obtained by the present invention has high mid-infrared transmittance and high hardness, meets the requirements of high-performance mid-infrared optical systems, and is suitable for the field of mid-infrared imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a spectral transmittance curve of the optical glass of Example 5 of the present invention in the range of 0.5 to 2.5 μm.
[0024] Figure 2 This is a spectral transmittance curve of the optical glass of Example 5 of the present invention at a wavelength greater than 2.5 μm but less than or equal to 5 μm. DETAILED DESCRIPTION
[0025] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.
[0026] [Optical glass]
[0027] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In this specification, unless otherwise specified, the content, total content and total content of each component are all expressed in mole percentage (mol%), and the total content of anions and cations of the glass components is 100%. In the description of the relationship between the contents of each component in the present invention, when it involves a multiplication and / or division relationship, the component content is calculated using the actual numerical value corresponding to its percentage. For example, when the component content percentage is 10%, it is calculated as 0.1 in the multiplication and / or division relationship.
[0028] Unless otherwise indicated in specific circumstances, the numerical ranges listed herein include upper and lower limits, "above" and "below" include endpoint values, and all integers or fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0029] It should be noted that the ionic valences of the components described below are representative values used for convenience and are not different from other ionic valences. The ionic valences of the components in the glass may be other than the representative values. For example, Ge usually exists in the glass in a state of +4 ionic valence, so in this patent, “Ge 4+ " is used as a representative value, but there is the possibility of existing in other ionic valence states, which is also within the scope of protection of this patent.
[0030] <Essential Components and Optional Components>
[0031] Ge 4+ In the present invention, it is a glass network former, which forms an irregular continuous network with the structural unit of [GeO4] tetrahedron, and is an essential component of the glass skeleton; as a network former, Ge 4+ The content of Ge has a great influence on the chemical stability; 4+ It is also an important component to ensure the high transmittance of glass in the infrared band. 4+ The content of Ge is lower than 13%, the above effect is not sufficient, and the chemical stability and mid-infrared transmittance of the glass cannot meet the design requirements; if Ge 4+ When the content of Ge is higher than 21%, the refractive index of the glass is low and the viscosity increases, resulting in deterioration of the fringes. 4+ The content of is 13 to 21%, preferably 14 to 20%, and more preferably 15 to 19%.
[0032] Ba 2+It can improve the refractive index and chemical stability of glass, and can also reduce the viscosity of glass, making it easier to clarify. 2+ The above effect is not sufficient if the content of Ba is lower than 4%. 2+ If the content of Ba is higher than 13%, the devitrification resistance of the glass will deteriorate and the glass will devitrify. 2+ The content is 4 to 13%, preferably 5 to 12%, and more preferably 6 to 11%.
[0033] Zn 2+ It can strengthen the glass network connection and improve the acid resistance and water resistance of the glass. 2+ The above effect is not sufficient if the content of Zn is less than 2%. 2+ When the content of Zn is higher than 10%, the refractive index of the glass decreases, and the surface tension of the glass is too large during the melting process, and the bubble level decreases. 2+ The content is 2 to 10%, preferably 3 to 9%, and more preferably 4 to 8%.
[0034] La 3+ It can increase the refractive index of glass, and also help to increase the hardness of glass and the transmittance of glass in the mid-infrared band. 3+ The above effect is not sufficient if the content of La is less than 3%. 3+ When the content of La is higher than 13%, the devitrification resistance of the glass deteriorates and the water resistance and acid resistance decrease. 3+ The content of is 3 to 13%, preferably 4 to 11%, and more preferably 5 to 10%.
[0035] After a lot of experimental studies, the inventors found that in some embodiments, if La 3+ The content of Zn 2+ and Ba 2+ Total content of Zn 2+ +Ba 2+ The ratio La 3+ / (Zn 2+ +Ba 2+ ) is less than 0.2, the hardness and refractive index of the glass decrease; if La 3+ / (Zn 2+ +Ba 2+ ) value is greater than 1.4, the chemical stability of the glass decreases and the tendency to devitrification increases. Therefore, in the present invention, La 3+ / (Zn 2+ +Ba 2+ ) is 0.2 to 1.4, and more preferably La 3+ / (Zn 2+ +Ba 2+ ) is 0.3 to 1.2, and La3+ / (Zn 2+ +Ba 2+ ) is 0.4~1.0.
[0036] Al 3+ It can enhance the network structure of glass and help improve the hardness and chemical stability of glass. However, if its content is too high, it will reduce the refractive index and mid-infrared transmittance of glass. 3+ The content is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.5%.
[0037] Ga 3+ It can enhance the network structure of glass and help improve the refractive index and chemical stability of glass. However, if its content is too high, the devitrification resistance of glass will be reduced. 3+ The content is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%.
[0038] After a lot of experimental studies, the inventors found that in some embodiments, if Ba 2+ The content of Ge 4+ , Ga 3+ 、Al 3+ Total content of Ge 4+ +Ga 3+ +Al 3+ The ratio between 2+ / (Ge 4+ +Ga 3+ +Al 3+ ) is less than 0.2, the melting temperature of the glass becomes higher, the production difficulty increases, the bubble degree becomes worse, and the refractive index is reduced and it is difficult to meet the design requirements; if Ba 2+ / (Ge 4+ +Ga 3+ +Al 3+ ) value is greater than 1.0, the devitrification resistance of the glass decreases, and the transmittance in the mid-infrared band decreases. Therefore, in the present invention, Ba 2+ / (Ge 4+ +Ga 3 + +Al 3+ ) is 0.2 to 1.0, more preferably Ba 2+ / (Ge 4+ +Ga 3+ +Al 3+ ) is 0.3~0.8.
[0039] F -During the melting process, it helps to remove structural water in the glass, reduce the phonon energy of the glass, improve the transmittance in the mid-infrared band, and also helps to reduce the viscosity of the glass, optimize the bubble degree of the glass, accelerate the melting of the glass powder, and improve the anti-crystallization performance of the glass. - When the content of F is less than 12%, the above effect is not sufficient; - If the content of F is too high, the refractive index of the glass will be reduced, and the glass components will be seriously volatilized during the melting process, thereby reducing the stability of the glass. - The content of is 12 to 22%, preferably 13 to 21%, and more preferably 14 to 20%.
[0040] After a lot of experimental studies, the inventors found that in some embodiments, if F - The content of Ba 2+ 、Zn 2+ ,La 3+ Total content of Ba 2+ +Zn 2+ +La 3+ The ratio F - / (Ba 2+ +Zn 2+ +La 3+ ) is less than 0.5, the melting temperature of the glass becomes higher, the production difficulty increases, the bubble content in the glass increases, and the transmittance in the mid-infrared band decreases significantly; if F - / (Ba 2+ +Zn 2+ +La 3 + ) is greater than 1.2, which leads to serious volatilization of glass components during the melting process, reduces the stability of the glass, and reduces the refractive index. Therefore, in the present invention, F is preferably - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.5 to 1.2, and more preferably F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.6 to 1.1, and more preferably F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.7~1.0.
[0041] O 2- It is a necessary component for forming the [GeO4] tetrahedral glass network skeleton structure and the [ZnO4] and [AlO4] tetrahedral network channels. 2- If the content of O is too low, the concentration of non-bridging oxygen structure increases, and the chemical stability and mechanical properties of the glass decrease.2- If the content of O is too high, the network structure of the glass will be more compact, the melting temperature will increase, and it will be difficult to control the stability of the components. 2- The content of is 43 to 52%, preferably 44 to 51%, and more preferably 45 to 50%.
[0042] After a lot of experimental studies, the inventors found that in some embodiments, if O 2- The content of F - The ratio between the contents of 2- / F - Less than 2.0, the hardness and chemical stability of the glass decrease; if O 2- / F - The value of is greater than 4.3, and there is structural water in the glass, which leads to a decrease in the transmittance in the mid-infrared band. 2- / F - It is 2.0 to 4.3, more preferably 2.1 to 3.9, and further preferably 2.3 to 3.5.
[0043] <Ingredients not contained>
[0044] In the glass of the present invention, transition metal components such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, even if contained in a small amount alone or in combination, will cause the glass to be colored and produce absorption at specific wavelengths in the mid-infrared region and the visible light region, thereby weakening the property of the present invention of improving the transmittance of mid-infrared and visible light. Therefore, it is preferably substantially free of these transition metal components, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0045] Components such as Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are actually not contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can also be manufactured, processed and discarded. At the same time, in order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As and Pb.
[0046] The "does not contain" and "0%" recorded in this article mean that the component is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing glass, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0047] Next, the properties of the optical glass of the present invention will be described.
[0048] <Refractive Index and Abbe Number>
[0049] The refractive index of glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in the national standard "GB / T 7962.1-2010".
[0050] In some embodiments, the refractive index (n d ) is 1.70 to 1.78, preferably 1.71 to 1.78, more preferably 1.72 to 1.78, and further preferably 1.74 to 1.77.
[0051] In some embodiments, the Abbe number (ν d ) is 42-51, preferably 42-49, more preferably 42-48, and further preferably 43-46.
[0052] The optical glass of the present invention has a relatively high refractive index, and the high refractive index optical glass can realize a large field of view and miniaturization of the optical system.
[0053] <Transmittance>
[0054] 0.5~2.5μm transmittance of glass (τ 0.5~2.5 ) According to the method specified in the national standard "GB / T7962.12-2010", the transmittance (τ 2.5~5 ) Tested according to the method specified in the national standard "GB / T 36403-2018".
[0056] In some embodiments, the optical glass of the present invention with a thickness of less than 2 mm has a transmittance of 0.5 to 2.5 μm (τ 0.5~2.5 ) is 83% or more, preferably 85% or more, and more preferably 87% or more.
[0057] In some embodiments, the optical glass of the present invention with a thickness of less than 2 mm has a transmittance (τ 2.5~5 ) is 78% or more, preferably 82% or more, and more preferably 85% or more.
[0058] In some embodiments, the wavelength (λ 50 ) is 5.75 μm to 5.8 μm, preferably 5.76 μm to 5.8 μm, and more preferably 5.77 μm to 5.8 μm.
[0059] The thickness of the glass is preferably 0.1 to 2 mm, more preferably 0.5 to 1.5 mm, further preferably 0.8 to 1.2 mm, and further preferably 0.3 mm, 0.5 mm, 1 mm, 1.2 mm, or 1.5 mm.
[0060] <Hardness>
[0061] The hardness of glass (H k ) Tested according to the method specified in the national standard "GB / T7962.18-2010".
[0062] In some embodiments, the hardness (H) of the optical glass of the present invention is k ) is 460×10 7 Pa or more, preferably 470×10 7 Pa or more, more preferably 480×10 7 Pa or more, more preferably 480×10 7 Pa~500×10 7 Pa.
[0063] <Water resistance stability>
[0064] Water resistance stability of glass (D W ) (Powder method) Tested in accordance with the method specified in the national standard "GB / T17129".
[0065] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.
[0066] <Acid resistance stability>
[0067] Acid resistance of glass (D A ) (Powder method) Tested in accordance with the method specified in the national standard "GB / T17129".
[0068] In some embodiments, the acid resistance stability (D A ) is 3 or more, preferably 2 or more.
[0069] <Bubble Degree>
[0070] The bubble degree of glass is tested according to the method specified in the national standard "GB / T7962.8-2010".
[0071] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.
[0072] [Method for producing optical glass]
[0073] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and processes, using raw materials including but not limited to oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), fluorides, etc., and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1500° C. for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0074] [Glass preforms and optical components]
[0075] The glass preform can be made from the produced mid-infrared transparent optical glass by means of grinding, or by means of compression molding such as re-hot pressing, precision stamping, etc. That is, the glass preform can be made by mechanical processing such as grinding and polishing the glass, or by making a preform for compression molding from optical glass, re-hot pressing the preform and then grinding the preform to make the glass preform, or by precision stamping the preform made by grinding. The present invention provides an optical element having the excellent characteristics of the above optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0076] The glass preform and the optical element of the present invention are both formed of the optical glass of the present invention. The mid-infrared transparent optical glass preform of the present invention has the excellent properties of optical glass, and the optical element of the present invention has the excellent properties of optical glass. Examples of lenses include various lenses such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, which have spherical or aspherical lens surfaces.
[0077] [Optical instruments]
[0078] The optical glass or optical element made of the optical glass in the present invention can be used to make optical instruments such as mid-infrared camera equipment, video equipment, display equipment and monitoring equipment.
[0079] Example
[0080] <Optical Glass Example>
[0081] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0082] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses with compositions shown in Tables 1 to 3. In addition, the properties of each glass are measured by the test method described in the present invention, and the test results are shown in Tables 1 to 3. 0.5~2.5 , τ 2.5~5 , 50 The glass thickness is 1 mm. The optical glass of Example 5 has a spectral transmittance curve of 0.5 to 2.5 μm. Figure 1 As shown, the optical glass of Example 5 has a spectral transmittance curve at a wavelength greater than 2.5 μm but less than or equal to 5 μm. Figure 2 shown.
[0083] Table 1.
[0084] Example (mol%) 1# 2# 3# 4# 5# 6# 7# 8# <![CDATA[Ge 4+ ]]> 13 15.4 17 18 16.5 19.2 15.3 19.9 <![CDATA[Ba 2+ ]]> 12.5 8.4 8.3 8.3 8.3 8.4 10.8 4.3 <![CDATA[Zn 2+ ]]> 4 5.2 8.3 5 5.1 4.1 4.3 4.5 <![CDATA[La 3+ ]]> 6.7 6 5.2 4 5.2 3.8 6.5 6.4 <![CDATA[Ga 3+ ]]> 0 0 0 0 0.7 0 0 0 <![CDATA[Al 3+ ]]> 0 0 0 0.7 0 0 0 0 <![CDATA[O 2- ]]> 50 49 45.2 48 48.6 48.8 47.8 51.3 <![CDATA[F - ]]> 13.8 16 16 16 15.6 15.7 15.3 13.6 total 100 100 100 100 100 100 100 100 <![CDATA[La 3+ / (Zn 2+ +Ba 2+ )]]> 0.406 0.441 0.313 0.301 0.388 0.304 0.430 0.727 <![CDATA[Ba 2+ / (Ge 4+ +Ga 3+ +Al 3+ )]> 0.962 0.545 0.488 0.444 0.483 0.438 0.706 0.216 <![CDATA[F - / (Ba 2+ +Zn 2+ +La 3+ )]]> 0.595 0.816 0.734 0.925 0.839 0.963 0.708 0.895 <![CDATA[O 2- / F - ]]> 3.623 3.063 2.825 3.000 3.115 3.108 3.124 3.772 <![CDATA[n d ]]> 1.76481 1.74322 1.73956 1.75238 1.76255 1.76002 1.75324 1.77562 <![CDATA[v d ]]> 43.20 44.18 45.29 44.56 43.85 44.03 44.51 42.31 <![CDATA[τ 0.5-2.5 (%)]]> ≥83.9 ≥85.0 ≥86.2 ≥86.2 ≥87.0 ≥86.9 ≥85.9 ≥84.1 <![CDATA[τ 2.5-5 (%)]]> ≥78.1 ≥81.9 ≥85.0 ≥84.5 ≥85.3 ≥85.2 ≥83.8 ≥80.2 <![CDATA[λ 50 (μm)]]> 5.75 5.78 5.79 5.79 5.78 5.8 5.79 5.77 <![CDATA[H K (×10 7 Well)]]> 460 476 481 472 495 482 474 499 <![CDATA[D A ]]> Category 2 Category 2 Category 2 Category 2 Category 2 Category 2 Category 2 Category 2 <![CDATA[D W ]]> Category 1 Category 1 Category 1 Category 1 Category 1 Category 1 Category 1 Category 1 Bubble degree (type) <![CDATA[A 00 ]]> <![CDATA[A 00 ]]> <![CDATA[A 00 ]]> <![CDATA[A 00 ]]> <![CDATA[A 00 ]]> <![CDATA[A 00 ]]> <![CDATA[A 00 ]]> <![CDATA[A0]]>
[0085] Table 2.
[0086]
[0087]
[0088] Table 3.
[0089]
[0090]
[0091] <Glass Preform Example>
[0092] The glass obtained from optical glass examples 1 to 24# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0093] <Optical Element Embodiment>
[0094] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0095] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0096] <Optical Instrument Embodiment>
[0097] The optical element obtained by the above optical element embodiment is optically designed and formed into an optical component or an optical assembly by using one or more optical elements. The optical component can be used in imaging devices in the field of mid-infrared imaging and sensing, for example.
Claims
1. Optical glass, characterized in that: Its components are expressed in molar percentage, and the cationic component contains: Ge 4+ :13~21%;Ba 2+ :4~13%; Zn 2+ : 2~10%; La 3+ : 3~13%; The anion component contains: O 2- :43~52%; F - :12~22%.
2. The optical glass according to claim 1, characterized in that: Its components are expressed in molar percentages, and the cationic component also contains: Al 3+ :0~2%;and / or Ga 3+ :0~3%.
3. Optical glass, characterized in that: Its composition is expressed in molar percentage, and the cation component is Ge 4+ :13~21%;Ba 2 + :4~13%; Zn 2+ : 2~10%; La 3+ :3~13%;Al 3+ :0~2%;Ga 3+ : 0~3%, the anion component is O 2- :43~52%; F - : Composition: 12~22%.
4. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: La 3+ / (Zn 2+ +Ba 2+ ) is 0.2 to 1.4, preferably La 3+ / (Zn 2+ +Ba 2+ ) is 0.3 to 1.2, and more preferably La 3+ / (Zn 2+ +Ba 2+ ) is 0.4~1.
0.
5. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, among which: Ba 2+ / (Ge 4+ +Ga 3+ +Al 3+ ) is 0.2 to 1.0, preferably Ba 2+ / (Ge 4+ +Ga 3+ +Al 3+ ) is 0.3~0.
8.
6. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.5 to 1.2, preferably F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.6 to 1.1, and more preferably F - / (Ba 2+ +Zn 2+ +La 3+ ) is 0.7~1.
0.
7. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: 2- / F - 2.0~4.3, preferably O 2- / F - 2.1 to 3.9, more preferably O 2- / F - It is 2.3 to 3.
5.
8. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: Ge 4+ : 14-20%, preferably Ge 4+ : 15-19%; and / or Ba 2+ : 5-12%, preferably Ba 2+ : 6-11%; and / or Zn 2+ : 3-9%, preferably Zn 2+ : 4-8%; and / or La 3+ : 4-11%, preferably La 3+ : 5-10%; and / or Al 3+ : 0~1%, preferably Al 3+ :0~0.5%;and / or Ga 3+ : 0-2%, preferably Ga 3+ :0~1%;and / or O 2- : 44-51%, preferably O 2- :45~50%;and / or F - : 13-21%, preferably F - :14~20%.
9. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d is 1.70 to 1.78, preferably 1.71 to 1.78, more preferably 1.72 to 1.78, and further preferably 1.74 to 1.77; Abbe number ν d It is 42-51, preferably 42-49, more preferably 42-48, and further preferably 43-46.
10. The optical glass according to any one of claims 1 to 3, characterized in that: The optical glass with a thickness of less than 2 mm and a transmittance of 0.5 to 2.5 μm 0.5~2.5 83% or more, preferably 85% or more, more preferably 87% or more; and / or a transmittance τ greater than 2.5 μm but less than or equal to 5 μm 2.5~5 is 78% or more, preferably 82% or more, more preferably 85% or more; and / or the wavelength λ corresponding to the mid-infrared transmittance of 50% 50 It is 5.75 μm to 5.8 μm, preferably 5.76 μm to 5.8 μm, and more preferably 5.77 μm to 5.8 μm.
11. The optical glass according to claim 10, characterized in that: The thickness of the optical glass is 0.1 to 2 mm, preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.3 mm, 0.5 mm, 1 mm, 1.2 mm, or 1.5 mm.
12. The optical glass according to any one of claims 1 to 3, characterized in that: The hardness H of the optical glass k 460×10 7 Pa or more, preferably 470×10 7 Pa or more, more preferably 480×10 7 Pa or more, more preferably 480×10 7 Pa~500×10 7 Pa; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A The degree of bubble is above Class 3, preferably Class 2 or above; and / or the degree of bubble is above Class A, preferably above Class A0, more preferably above Class A 00 class.
13. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 12.
14. An optical element, characterized in that The optical glass is made of the optical glass described in any one of claims 1 to 12, or the glass preform described in claim 13.
15. An optical instrument, characterized in that A method of manufacturing an optical glass comprising the optical glass according to any one of claims 1 to 12, or a method of manufacturing an optical element comprising the optical glass according to claim 14.
Citation Information
Patent Citations
Optical glass, optical elements and preformed articles for precise pressurization shaping
CN101792258A
Infrared optical glass for precise compression molding
CN103058517A
Infrared transmitting germanate glass containing fluoride
CN1375471A
Improvements in and relating to fibre-optical elements
GB1108509A
Optical glass, optical element and preform
JP2010235429A